2004
DOI: 10.1073/pnas.0406571101
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of a functionally enhanced GFP-tagged galanin R2 receptor in PC12 cells: Constitutive and ligand-induced internalization

Abstract: Trafficking of the galanin R2 receptor (GALR2) fused with enhanced GFP (EGFP) was studied by using confocal fluorescence microscopy. The fusion protein was predominantly localized on the plasma membrane with some intracellular fluorescent structures (vesicles), mainly in the perinuclear region. Incubation with galanin resulted in a concentration-dependent increase in intracellular Ca 2؉ concentration levels, suggesting that the GALR2-EGFP conjugate is functional. After blocking endocytosis with methyl-␤-cyclod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 49 publications
3
39
0
Order By: Relevance
“…Although constitutive internalization in the absence of a ligand has been reported for several GPCRs (19,(24)(25)(26)(27)(28), to our knowledge no indication of this phenomenon has been provided for ORs. Our present results indicate that receptor internalization, which is an agonist-dependent process in the classical model of GPCR signaling, can also occur without G protein activation and suggest that GPCRs can adopt many more conformational states than is usually believed (29).…”
Section: Discussionmentioning
confidence: 69%
“…Although constitutive internalization in the absence of a ligand has been reported for several GPCRs (19,(24)(25)(26)(27)(28), to our knowledge no indication of this phenomenon has been provided for ORs. Our present results indicate that receptor internalization, which is an agonist-dependent process in the classical model of GPCR signaling, can also occur without G protein activation and suggest that GPCRs can adopt many more conformational states than is usually believed (29).…”
Section: Discussionmentioning
confidence: 69%
“…This effect resembled wild-type MEFs treated by monensin, an inhibitor of the recycling trafficking (53,54). Furthermore, the partially restored MMP2 secretion in rescued Rab11a null MEFs was sensitive to the blockage by monensin (Fig.…”
Section: D Live Cell Fluorescent Analyses Of Wild-type and Rab11amentioning
confidence: 89%
“…Studies using cell lines transfected with galanin receptors have demonstrated GAL 1 homodimerization and internalization (Wang et al, 1998b;Xia et al, 2004Xia et al, , 2005bXia et al, , 2008Wirz et al, 2005). GAL 2 also undergoes internalization upon ligand binding (Xia et al, 2004(Xia et al, , 2005b.…”
Section: A Identification and Nomenclaturementioning
confidence: 99%
“…This allowed the mapping of galanin receptor transcripts using Northern blotting, qRT-PCR (Waters and Krause, 2000), and in situ hybridization (O'Donnell et al, 1999Burazin et al, 2000;Mennicken et al, 2002;Le Maître et al, 2013). Thus far, no totally specific and reliable antigalanin receptor antibodies have been generated (Lu and Bartfai, 2009), so the exact regional and cellular localization of the three galanin receptor proteins in brain and other tissues remains to be elucidated, although studies of tagged receptors in transfected cell lines have provided some information on trafficking of GAL 1 and GAL 2 (Xia et al, 2004Wirz et al, 2005).…”
Section: B History Of Galanin Researchmentioning
confidence: 99%